Trade liberalization and complementary domestic policies: a rural-urban general equilibrium analysis of Morocco. - Lofgren, Hans; El-Said, Moataz; Robinson, Sherman (International Food Policy Research Institute, 1999)
In this study, a dynamically recursive general equilibrium model of Morocco is used to examine alternative trade and domestic policy scenarios involving the implementation of the EU Association Agreement for the period 1998-2012. The model has a detailed treatment of the agricultural and rural economy in Morocco. The results for the trade liberalization scenarios indicate that tariff unification has small aggregate effects whereas the removal of non-tariff barriers has strong positive aggregate effects: factor incomes and household welfare expand considerably more rapidly than for the base. However, trade liberalization disfavors the rural poor, especially in rainfed areas. We simulate the introduction of complementary domestic policies with a non-distorting transfer program that fully compensates the owners of rainfed resources and skill upgrading for the rural labor force. The results indicate that, if combined with at least one of these complementary domestic policies, trade liberalization can lead to a win-win outcome: the welfare of all household groups increases significantly more rapidly than if status-quo policies are followed.